Building Happiness Indicators Some Philosophical and Political Issues - Landes, Xavier (Les ateliers de l'éthique / The Ethics Forum, 2015)
Happiness has become a central theme in public debates. Happiness indicators illustrate this importance. This article offers a typology of the main challenges conveyed by the elaboration of happiness indicators, where happiness can be understood as hedonia, subjective well-being, or eudaimonia. The typology is structured around four questions: (1) what to measure?—i.e., the difficulties linked to the choice of a particular understanding of happiness for building an indicator; (2) whom to include?—i.e., the limits of the community monitored by such an indicator; (3) how to collect the data?—i.e., the difficulties stemming from objective and subjective reporting; (4) what to do?—i.e., the concerns about the use of happiness indicators in public policy. The major points of normative contention are discussed for each of these dimensions. The purpose of this article is to contribute in a constructive manner to happiness research by offering an overview of some major philosophical and political challenges of building happiness indicators. The conclusion underlines the importance of the strategy of diversification- hybridization, which consists in setting a variety of indicators or composite indicators that articulate different understandings of happiness. It is stressed that happiness indicators raise democratic and institutional issues with which normative thinkers should deal.